2017
DOI: 10.1111/jdv.14095
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of an emollient cream in the treatment of xerosis in diabetic foot: a double‐blind, randomized, vehicle‐controlled clinical trial

Abstract: Treatment with an emollient is effective for improving foot xerosis in patients with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
0
10
0
3
Order By: Relevance
“…Although the current clinical pharmacology study was not designed to assess therapeutic benefits associated with the products, the findings from the current study provide pharmacological evidence for the observed therapeutic benefits associated with V0034CR. Other randomized clinical trials have shown that V0034CR reduces the severity of ichthyosis in children, and improves xerosis in children with AD and in patients with diabetic foot, reduces flares and corticosteroid consumption, and reduces the severity of symptoms in children with mild‐to‐moderate AD …”
Section: Discussionmentioning
confidence: 99%
“…Although the current clinical pharmacology study was not designed to assess therapeutic benefits associated with the products, the findings from the current study provide pharmacological evidence for the observed therapeutic benefits associated with V0034CR. Other randomized clinical trials have shown that V0034CR reduces the severity of ichthyosis in children, and improves xerosis in children with AD and in patients with diabetic foot, reduces flares and corticosteroid consumption, and reduces the severity of symptoms in children with mild‐to‐moderate AD …”
Section: Discussionmentioning
confidence: 99%
“…The first author (KF) described the adverse effects of daily sole washing, the risk area of the skin between the toes, and the importance of applying ointments after wiping or washing the skin to avoid stacking ointment. Foot hygiene was covered in the program and has been reported previously [38,39]; however, it was not included in the practice session due to the providers' work circumstances.…”
Section: Discussionmentioning
confidence: 99%
“…The xerosis assessment scale, [8][9][10][11] overall cutaneous score, 9,10 dryness area severity index score, 12 transepidermal water loss, 13 and skin hydration 13 have been used as indicators of dry skin. Skin hydration is affected by the amount of moisture in the stratum corneum, and can be used to quantitatively assess the severity of dry skin.…”
Section: Oe Et Almentioning
confidence: 99%